PTH-103 Epidemiology of vitamin D deficiency and bone mineral density in patients with chronic liver disease. (8th June 2018) - Rhodes, Freya; Greenham, Olivia; Hunt, Emma; Kearney, Orla; Patch, David; Ryan, Jennifer; Westbrook, Rachel
Abstract : Introduction: Patients with chronic liver disease have increased risk of bone disease (BD) with reported prevalence of osteoporosis (OP) between 12%–55% and a high prevalence of Vitamin D deficiency. The aetiology is poorly understood with a complex interplay between endocrine, metabolic, nutritional and physical abnormalities. We aim to evaluate the influence of epidemiological parameters on bone mineral density and vitamin D levels in cirrhotics. Methods: Retrospective study of cirrhotic patients from 2016–2017. Data were collected on aetiology of cirrhosis, severity (UKELD/MELD score), bone mineral density (BMD), vitamin D, body mass index (BMI) and hand grip strength. OP was defined as per WHO classification and Vitamin D deficiency as a Vitamin D level <50 nmol/L with severe deficiency <25 nmol/L. Results: 248 patients were included, 180 male, 58 female, median age 57 years (IQR 49–63) and median BMI of 27. Underlying aetiology was ALD (n=78), Viral (n=56), PBC/PSC (n=46), NAFLD (n=23) and AIH (n=18). Median UKELD and MELD scores overall were 53 (IQR 49–57) and 14 (IQR 10–19). At the time of evaluation 141 (56.8%) patients were either osteoporotic (n=52) or osteopenic (n=99). The prevalence of BD was significantly higher in cholestatic diseases (71.7%, mean T score −1.86 +/1.22) and lower in NAFLD (37%, mean T score −0.45+/-1.50) when compared to other aetiologies (ANOVA p=0.0005). 120 (55.4%) patients were vitamin D deficient with 51 (25%) patients having severe deficiency. Mean vitamin D level was highest in cholestatic disease (75.5 ng/ml +/59.6) when compared to other aetiologies (ANOVA p=0.003). Liver severity scores (UKELD/MELD respectively) did not correlate with the presence of BD (p=0.32/p=0.53) but patients with higher MELD scores had lower vitamin D levels (p=0.04). Reduced BMI correlated with the presence of BD (p<0.01) but not vitamin D level. Increased Hand Grip Strength (HGS) was associated with higher vitamin D levels (p=0.049) and higher lumbar T scores (p=0.014). Vitamin D levels did not correlate with BMD (p=0.77). Conclusion: Bone disease and vitamin D deficiency are prevalent in patients with cirrhosis, with cholestatic aetiologies having the highest prevalence of OP and NAFLD the lowest. Interestingly disease severity does not correlate with BD whereas more functional markers of frailty such as HGS appear to positively correlate. Increased disease severity (MELD) significantly correlates with decreasing vitamin D levels, which raises the question of whether vitamin D could be impacting on progression of cirrhosis, or vice versa. Further prospective research is needed to look at the role of vitamin D in cirrhosis.